(untitled) (INSLA E-Proceedings, 2020)
COVID-19 pandemic is not only a significant threat to public health. It also has a serious economic impact on people’s livelihood including indigenous peoples or Orang Asli communities in Peninsular Malaysia even though they are living far away in rural areas, such as in protected areas. This paper aims to share our observation on an Orang Asli community in Kampung Peta, which is located at the entrance of Endau Rompin National Park, Johor, Malaysia. The research is based on a preliminary observation and casual conversation with the villagers in a recent visit. From our short visit to the village in March 2020, we found that even before the Restricted Movement Order (RMO) was implemented, the pandemic has impacted the livelihood of Kampung Peta people whose income are also dependent on tourism activities in the national park. With the effect of COVID-19 expected to last for years to come, it is important to ensure the policy development addresses the minority community groups who live in the rural area including the national park.